The Evolutionary Fate of Alternatively Spliced Homologous Exons after Gene Duplication - Abascal, Federico (Genome Biol Evol, 2015)
Alternative splicing and gene duplication are the two main processes responsible for expanding protein functional diversity. Although gene duplication can generate new genes and alternative splicing can introduce variation through alternative gene products, the interplay between the two processes is complex and poorly understood. Here, we have carried out a study of the evolution of alternatively spliced exons after gene duplication to better understand the interaction between the two processes. We created a manually curated set of 97 human genes with mutually exclusively spliced homologous exons and analyzed the evolution of these exons across five distantly related vertebrates (lamprey, spotted gar, zebrafish, fugu, and coelacanth). Most of these exons had an ancient origin (more than 400 Ma). We found examples supporting two extreme evolutionary models for the behaviour of homologous axons after gene duplication. We observed 11 events in which gene duplication was accompanied by splice isoform separation, that is, each paralog specifically conserved just one distinct ancestral homologous exon. At other extreme, we identified genes in which the homologous exons were always conserved within paralogs, suggesting that the alternative splicing event cannot easily be separated from the function in these genes. That many homologous exons fall in between these two extremes highlights the diversity of biological systems and suggests that the subtle balance between alternative splicing and gene duplication is adjusted to the specific cellular context of each gene.